Identification of migratory waterbirds hotspot pattern as bioindicator of ecotourism management in Pulau Kukup National Park - Kamarudin, Ika Safika (2022)
The link between tourism and conservation has been strengthened and expanded through ecotourism. Mainly, ecotourism destination is often found in areas with abundant natural resources including mangroves areas. In the context of Pulau Kukup National Park, however, there is lack of exposure on using migratory waterbirds as bioindicator for ecotourism activity that might cause harm to the environment and its ecosystem. Thus, this study aims to examine migratory waterbirds hotspot pattern as bioindicator to ecotourism activity in Pulau Kukup National Park. The objectives of this study are to explore the characteristics of migratory waterbird physical environment condition, to analyze the migratory waterbird distribution pattern, and to propose potential significant action plan in protecting the distribution pattern of migratory waterbirds in Pulau Kukup National Park ecotourism management. This study applied a qualitative research method together with secondary data. Informant interviews and site observation were used to evaluate the current condition of the physical environment and the migratory waterbird species. The major findings of this study show that this area is rich in bird species and serves as a shelter for migratory waterbirds. However, lack of proper ecotourism management can cause the destruction of migratory waterbird distribution patterns and indirectly can cause harm to the ecosystem. The result implies a need to enhance the management of this park that indirectly can protect migratory waterbird distribution patterns and ecotourism resources in Pulau Kukup National Park. This study concluded that effective management and proper development, infrastructure, technologies implementation can highly benefit the management and also the environment.